Thermal properties of the hanging wall of the central Alpine Fault, New Zealand. Issue 4 (2nd October 2021) - Janku-Capova, Lucie; Sutherland, Rupert; Townend, John; Lin, Weiren
ABSTRACT: Samples of schist, protomylonite, mylonite and ultramylonite from the hanging wall of New Zealand's Alpine Fault were measured using a transient plane source, yielding mean bulk thermal conductivity of 2.04 ± 0.33 W m –1 K –1 in a dry state and 2.78 ± 0.51 W m –1 K –1 in a wet state at room temperature. Corresponding thermal diffusivity is 1.35 ± 0.32×10 –6 m 2 s –1 in a dry state and 1.72 ± 0.27×10 –6 m 2 s –1 in a wet state. Thermal conductivity and diffusivity calculated from the mineralogical composition of cuttings from the DFDP-2B borehole in Whataroa Valley and previously published thermal properties of minerals are 3.26 ± 0.16 W m –1 K –1 and 1.56 ± 0.08×10 –6 m 2 s –1, respectively. We attribute the significant difference in thermal conductivity to regional mineralogical variations in composition of rock samples versus borehole cuttings. Anisotropy of thermal properties is inferred to exist on a centimetre scale, due to competing effects of aligned quartz veins, minerals, and microfractures; but our measurements do not confirm significant anisotropy. Radiogenic heat productivity calculated from geochemical data and a gamma log in DFDP-2B (1.8–2.1 μW m –3 ) falls within the previously reported range for greywacke and schist.